ANÁLISE E DIAGNÓSTICO DE UMA UNIDADE DE PRODUÇÃO LEITEIRA, NO MUNICIPIO DE BOA VISTA DO CADEADO - Kleemann, Ana P. H.; Uhde, Leonir T.; Basso, Nilvo; Henriques, Angélica d. O.; Martins, Luciane R. V.; Correa, Maira A. (Salão do Conhecimento, 2013)
Resumo